PARTITIONING OF FLORISTIC-STRUCTURAL VARIATION OF THE TREE COMPONENT IN AN ALLUVIAL ARAUCARIA FOREST IN SOUTHERN BRAZIL - Loebens, Rodineli (2018)
This study aimed to evaluate the influence of spatial structure and environmental variables on floristic-structural organization of the tree component, in an Alluvial Araucaria Forest, in southern Brazil. To do so, 48 200 m2 sampling units were allocated in the study area, located in the municipality of Lages, SC state. All trees within the sampling units, with diameter at breast height (dbh) equal to or greater than 5 cm were identified. The environmental and spatial variables were measured in each sampling unit. The data were analyzed through Mantel Correlogram, Variation Partitioning, Redundancy Analysis, analysis of Principal Coordinates of Neighbor Matrices and correlation tests. A total of 1,462 individuals, belong to 66 species, were sampled. Together, the environmental and spatial variables explained 24.13% of total variation, with the largest part (15.22%) being spatially structured. The significant environmental variables were topography (maximum elevation difference) and fertility (bases sum and P). It is possible to conclude that the tree component is organized as a floristic-structural gradient. Furthermore, the results suggest that the inundation regime and the presence of flood prone areas were relevant for micro-habitat definitions, that influenced the distribution of species